Local Content Policies in the Russian Higher Education Sector: Harming or Aiding Internationalization? - Anne Crowley-Vigneau; Andrey Baykov; Yelena Kalyuzhnova; Vera Gnevasheva (Вопросы образования, 2021)
Tensions between modernization and stability in Russia have been widely analyzed in the economic and political spheres; yet in the higher education sector, studies have mainly focused on the dominant internationalization discourse and left the demand for support and stability in universities understudied. This paper analyzes the friction between modernization and stability in educational policies, identifying the difficulties experienced when internationalizing universities and the opportunities for national governments to support academics. Through a case study devoted to the Russian higher education sector, the authors establish that the rules adopted by the government to ensure that internationalization processes are beneficial to Russian universities and to the country as a whole bear a striking similarity with Local Content policies in other spheres. The survey of Russian academics conducted by the authors reveals that the large acceptance among them of internationalization of higher education is accompanied by expectations that the state will help with capacity building and protect them from the negative aspects of a rapid integration into the international educational space. An analysis of the findings points out the benefits and risks of helping universities and their staff in the transition to international competition. Adequately calibrated LC policies are shown to aid the internationalization of higher education as they help “rub the edges off” an intensive catch-up internationalization program and support what is a “fledgling industry” in its transition to international competition.